(untitled) (Conferencea, 2021)
Much emphasis has been placed in the higher education literature, to the understanding of the manner and process of providing education in the accounting discipline. Specifically, the emphasis on using innovative teaching practices such as information and communication technologies, the Internet as well as various computer programs, simulations, case studies on real and virtual work environments, have been investigated in an attempt to understand current demands and move the discipline forward. Following a thorough review of the relevant literature, this study aims to identify and present different views and research findings on the key issue of teaching accounting, internationally. The findings suggest that despite the availability of the former teaching practices, students mainly prefer personalized teacher-centered methods; they also recommend the aforementioned practices as ancillary tools to the traditional method, rather than key learning tools in the courses taken. These findings have obvious implications for the design of accounting course curricula by professional bodies and/or Higher Education Institutions in order to help graduates meet and adapt to the demands for professional competency development in the accounting field.